Cover Image. (28th November 2018) - Wang, Junhua; Jebbawi, Fadi; Bellanger, Anne‐Pauline; Beldi, Guido; Millon, Laurence; Gottstein, Bruno
Abstract : The cover image is based on the Original Paper Immunotherapy of alveolar echinococcosis via PD‐1/PD‐L1 immune checkpoint blockade in mice by Junhua Wang et al., https://doi.org/10.1111/pim.12596 .